Functional network pipeline reveals genetic determinants associated with in situ lymphocyte proliferation and survival of cancer patients - Mlecnik, Bernhard; Bindea, Gabriela; Angell, Helen K.; Sasso, Maria Stella; Obenauf, Anna C.; Fredriksen, Tessa; Lafontaine, Lucie; Bilocq, Amelie M.; Kirilovsky, Amos; Tosolini, Marie; Waldner, Maximilian; Berger, Anne; et al. (Science Translational Medicine, 2014)
The tumor microenvironment is host to a complex network of cytokines that contribute to shaping the intratumoral immune reaction. Chromosomal gains and losses, coupled with expression analysis, of 59 cytokines and receptors and their functional networks were investigated in colorectal cancers. Changes in local expression for 13 cytokines were shown. Metastatic patients exhibited an increased frequency of deletions of cytokines from chromosome 4. Interleukin 15 (IL15) deletion corresponded with decreased IL15 expression, a higher risk of tumor recurrence, and reduced patient survival. Decreased IL15 expression affected the local proliferation of B and T lymphocytes. Patients with proliferating B and T cells at the invasive margin and within the tumor center had significantly prolonged disease-free survival. These results delineate chromosomal instability as a mechanism of modulating local cytokine expression in human tumors and underline the major role of IL15. Our data provide further mechanisms resulting in changes of specific immune cell densities within the tumor, and the importance of local active lymphocyte proliferation for patient survival.
EVALuna2:1872